Instrumentation for the surface measurements of atmospheric electrical parameters at Maitri, Antarctica: first results - Panneerselvam, C.; Kumar, C.P. Anil; Dhar, Ajay; Nair, K.U.; Selvaraj, C.; Gurubaran, S.; Pathan, B.M. (My University, 2010)
We are operating atmospheric electrical instruments like long wire antenna, electric field meter, wire antenna and passive antenna for atmospheric Maxwell current, electric field, conduction current and atmospheric potential gradient. This year (December 2008) we have installed Electric Field Meter (EFM-100) and wire antenna for measuring the atmospheric electric field and conduction current. This instrument is deployed at Maitri, Antarctica and will be operated under any weather conditions like snow fall and strong blizzard etc. The study have been carried out during austral summer for the period of 2008 and 2009 at the Indian station, Maitri (70.75◦S, 11.75◦E, 117 m above mean sea level). The present work has been to understand the new instrument system in response to different meteorological conditions and on fairweather days. In this paper we have selected the data of the days during magnetically quiet period to minimize the upper atmospheric contribution. Fairweather’ conditions, i.e., days with absence of high winds, drifting or falling snow and clouds. The diurnal variation curve of electric field during fairweather days is a single periodic with a minimum at 04:00 UT and a maximum at 19:00 UT. But atmospheric current variation has minimum 03:00 UT for Maxwell current and conduction current. The maximum for Maxwell current is at 20:00 UT and 19:00 UT for the conduction current, which is very similar to the Carnegie curve. The measured electric field from the Passive antenna and EFM-100 compared and is behaving similar variation. Using Maxwell current density and conduction current density we have separated the displacement current density.
Keywords: Maitri; Antarctica; Atmospheric electrical parameters; Atmospheric electricity; GEC; Global electric circuit; Displacement current; Conduction current; Electric field; Maxwell current; Fairweather day